Perjanjian Jual Beli Tanah Berdasarkan Hukum Adat di Desa Sungai Sayang Kecamatan Sadu Kabupaten Tanjung Jabung Timur - Maryati, Maryati; Mahila, Syarifa; Restarum, Triamy; Puspita, Sri Ayu Indah (Wajah Hukum, 2025)
This study aims to explore and analyze the implementation of land sale and purchase agreements based on customary law in Sungai Sayang Village, Sadu Subdistrict, Tanjung Jabung Timur Regency, as well as to examine the legal strength of such agreements from the perspective of national law. In customary communities, land transactions are not only guided by formal legal principles but are also deeply rooted in local norms and traditions that have been passed down through generations. This research employs an empirical juridical approach using qualitative methods. Data were collected through interviews with traditional leaders, village officials, and community members who have engaged in land transactions, as well as through a review of relevant documents. The findings reveal that land sale and purchase processes in Sungai Sayang Village are typically conducted orally, witnessed by customary leaders and local witnesses, and accompanied by symbolic gestures as a sign of a valid agreement. Although unwritten, such agreements are deemed legitimate and binding under customary law.However, from the perspective of national law, these agreements do not carry full legal force unless formalized through an authentic deed in accordance with applicable statutory regulations. Therefore, it is necessary to harmonize customary law with positive (national) law to ensure that community land rights are protected and future disputes are prevented